Emerging role of microtubule-associated proteins on cancer metastasis - Wattanathamsan, Onsurang; Pongrakhananon, Varisa (Frontiers in Pharmacology, 2022)
The major cause of death in cancer patients is strongly associated with metastasis. While much remains to be understood, microtubule-associated proteins (MAPs) have shed light on metastatic progression’s molecular mechanisms. In this review article, we focus on the role of MAPs in cancer aggressiveness, particularly cancer metastasis activity. Increasing evidence has shown that a growing number of MAP member proteins might be fundamental regulators involved in altering microtubule dynamics, contributing to cancer migration, invasion, and epithelial to mesenchymal transition. MAP types have been established according to their microtubule-binding site and function in microtubule-dependent activities. We highlight that altered MAP expression was commonly found in many cancer types and related to cancer progression based on available evidence. Furthermore, we discuss and integrate the relevance of MAPs and related molecular signaling pathways in cancer metastasis. Our review provides a comprehensive understanding of MAP function on microtubules. It elucidates how MAPs regulate cancer progression, preferentially in metastasis, providing substantial scientific information on MAPs as potential therapeutic targets and prognostic markers for cancer management.